Risk of Venous Thromboembolism in Transgender People Undergoing Hormone Feminizing Therapy: A Prevalence Meta-Analysis and Meta-Regression Study - Totaro, Maria; Palazzi, Sara; Castellini, Chiara; Parisi, Antonio; D’Amato, Federica; Tienforti, Daniele; Baroni, Marco Giorgio; Francavilla, Sandro; Barbonetti, Arcangelo (Frontiers in Endocrinology, 2021)
Background: Although venous thromboembolism (VTE) is a recognized side effect of some formulations of estrogen therapy, its impact in transgender people remains uncertain. The aim of this study was to define pooled prevalence estimate and correlates of VTE in Assigned Males at Birth (AMAB) transpeople undergoing gender affirming hormone therapy. Methods: A thorough search of MEDLINE, COCHRANE LIBRARY, SCOPUS and WEB OF SCIENCE databases was carried out to identify suitable studies. Quality of the articles was scored using the Assessment Tool for Prevalence Studies. Data were combined using random effects models and the between-study heterogeneity was assessed by the Cochrane's Q and I2. Results: the eighteen studies included gave information about 11,542 AMAB undergoing gender affirming hormone therapy. The pooled prevalence of VTE was 2% (95%CI:1-3%), with a large heterogeneity (I2=89.18%, P<0.0001). Trim-and-fill adjustment for publication bias produced a negligible effect on the pooled estimate. At the meta-regression analysis, a higher prevalence of VTE was significantly associated with an older age (S=0.0063; 95%CI:0.002,0.01,P=0.002) and a longer length of estrogen therapy (S=0.0011; 95%CI:0.0006,0.001,P<0.0001). When, according to the meta-regression results, the analysis was restricted to series with a mean age ≥37.5 years, the prevalence estimate for VTE increased up to 3% (95%CI:0-5%), but with persistence of a large heterogeneity (I2=88,2%, P<0.0001); studies on younger participants (<37.5 years) collectively produced a pooled VTE prevalence estimate of 0% (95%CI:0-2%) with no heterogeneity (I2=0%, P=0.97). Prevalence estimate for VTE in series with a mean length of estrogen therapy ≥53 months was 1% (95%CI:0-3%), with persistent significant heterogeneity (I2=84,8%, P=0.0006); studies on participants subjected to a shorter length of estrogen therapy (<53 months), collectively produced a pooled VTE prevalence estimate of 0% (95%CI:0-3%) with no heterogeneity (I2=0%, P=0.76). Conclusions: The overall rate of VTE in AMAB transpeople undergoing gender affirming hormone therapy was 2%. In AMAB population with <37.5 years undergoing estrogen therapy for less than 53 months, the risk of VTE appears to be negligible. Further studies are warranted to assess whether different types and administration routes of estrogen therapy could decrease the VTE risk in AMAB transpeople over 37.5 years subjected to long-term therapy.